2021
DOI: 10.1039/d1ob00798j
|View full text |Cite
|
Sign up to set email alerts
|

The microenvironment and pKa perturbation of aminoacyl-tRNA guided the selection of cationic amino acids

Abstract: The proteinogenic lysine (Lys) and arginine (Arg) have multiple methylene groups between α-carbon and terminal charged centre. Why nature did not select ornithine (Orn), 2,4-diamino butyric acid (Dab) and 2,3-diamino...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…The possibility of Hbonding between the N−H of α-amine and the carbonyl of LysOct was suggested earlier. 44,54 In the presence of DA, the N−H of α-amine likely engaged in H-bonding with the carboxylate (COO − ), and therefore, the H-bonding probability to ester carbonyl may be reduced. The PXRD measurements of LysOct, DA, and LysOct−DA were carried out (Figure S28).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The possibility of Hbonding between the N−H of α-amine and the carbonyl of LysOct was suggested earlier. 44,54 In the presence of DA, the N−H of α-amine likely engaged in H-bonding with the carboxylate (COO − ), and therefore, the H-bonding probability to ester carbonyl may be reduced. The PXRD measurements of LysOct, DA, and LysOct−DA were carried out (Figure S28).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have recently shown that a loosely packed micellar surface of LysOct can catalyze amide bond formation under physiological conditions. 44 We used the vesicular surface to carry out peptide formation at pH 7.0, 37 °C. Leucine phenolic ester (LP) was synthesized as a model aa-tRNA mimic and acylating agent to form peptide bonds with amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations